An unusual presentation of very early onset metastatic pancreatic adenocarcinoma in a young man: case report - Arora, Abhishek; Jha, Ashesh K.; Kumar, Manoj; Kumar, Manoj (International Surgery Journal, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is rare below 45 years of age and usually presents with constitutional symptoms, pain and jaundice. A 25 year old man, non-smoker, non-alcoholic presented to us with a lump in central upper abdomen of 1 month duration. Abdominal examination revealed a hard epigastric mass of size 7×10 cm. There were no other associated symptoms and no history of any similar illnesses in the family members. All laboratory parameters were within normal limits. Computed tomography showed a heterogeneous mass of size 7×13×15 cm arising from the head and neck of pancreas abutting the anterior abdominal wall with multiple abdominal and pelvic peritoneal deposits. Ultrasound guided core needle biopsy suggested PDAC. Hence, a diagnosis of very early onset metastatic PDAC was rendered and the patient was referred for palliative chemotherapy. PDAC below 45 years of age is known as very early onset PDAC. It is usually associated with family history of PDAC and known risk factors. This case was unique because of absence of the characteristic clinical features and known risk factors, early onset of occurrence and negative family history, which led to a diagnostic dilemma.